Green Energy and Environmental Impact on the Industrial Sector in 33 High-Income Countries - Muhammad Waseem; Sania Batool (iRASD Journal of Energy & Environment, 2023)
This study analyzes the influence of adequate electricity supply on the industrial sector in developing nations, utilizing panel data from 2000 to 2022. Contrary to original beliefs, the study examines industry output as the dependent variable, with renewable energy as the main explanatory factor. The study incorporated control variables such as CO2 emissions, government expenditure, GDP per capita, labor force participation, and gross capital formation. The investigation included panel Autoregressive Distributed Lag (ARDL) models, unit root tests, and causality tests. In emerging countries, industrial growth is positively impacted by government spending, labor force involvement, CO2 emissions, and GDP per capita. Developed countries demonstrate favorable impacts on industrial growth through gross fixed capital formation, renewable energy, and other factors, as indicated by the long-term outcomes of the ARDL method. Policymakers in developing nations may contemplate raising government spending in pertinent sectors, encouraging worker engagement, and enacting laws to decrease CO2 emissions based on these findings. Developed countries' authorities should prioritize improving gross fixed capital creation, integrating more renewable energy sources, and sustaining factors boosting industry growth.